PORNOGRAFI DI MEDIA MASSA INDONESIA - Wijaya, Sri Herwindya Baskara (KOMUNITAS)
Ethic actually is a dialog between freedom and responbility, between destination and methods to get it. Although there are regulation toregulate about proffesion ethic, but media user often donât follow it. We can see from news in mass media which is saw not suitableÂ withÂ ethicÂ codeÂ inÂ regulation.Â OneÂ ofÂ itÂ isÂ connectedÂ withÂ pornography publication in mass media. The interest to get maximal capital is one cause of it. The effect, public become victims from it especially cildren and adolescent.Â Based on the introduction,Â theÂ issuesÂ raisedÂ inÂ thisÂ articleÂ isÂ howÂ theÂ imageÂ ofÂ pornographic publicationsÂ inÂ massÂ mediaÂ inÂ IndonesiaÂ areÂ consideredÂ toÂ violateÂ theÂ formal journalistic code of ethics applicable. The expected goals of writing this article is to find a picture pornographic publications in mass media in Indonesia are considered to violate the formal journalistic code of ethics applicable.Keywords : Ethic, regulation, pornograph, mass media, capital